The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1007/bf02189495
|View full text |Cite
|
Sign up to set email alerts
|

Fate and effects of cadmium in an experimental marine ecosystem

Abstract: Two recirculated marine seawater systems (capacities: 150 and 300 1) were used for the study on cadmium accumulation of biological filter sludge, by the mussel Mytilus edulis and the plaice Pleuronectes platessa for a period of up to 300 days. In the contaminated system Cd concentrations varied from 2.5 to 7.0 #g/1 with a mean of 4.6 + 1.15 #g/1 (control: 1.04 + 0.46 #g/l). Accumulation of Cd by the filter sludge from the control system as well as from the contaminated system was significant. Mean concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Many of these signs of ascorbic acid deficiency are also characteristic of cadmium poisoning. The growth rate decreases, anaemia and haemorrhages develop, fin regeneration is delayed, and the skeleton becomes deformed in cadmium intoxicated fish (Cearley & Coleman, 1974;Larsson, 1975;Weis & Weis, 1976;Westernhagen et al, 1978Westernhagen et al, , 1980. Hepatic cytochrome P-450 levels fall in rats exposed to cadmium (Schnell et al, 1979) and also in scorbutic guinea pigs (Omaye & Turnbull, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these signs of ascorbic acid deficiency are also characteristic of cadmium poisoning. The growth rate decreases, anaemia and haemorrhages develop, fin regeneration is delayed, and the skeleton becomes deformed in cadmium intoxicated fish (Cearley & Coleman, 1974;Larsson, 1975;Weis & Weis, 1976;Westernhagen et al, 1978Westernhagen et al, , 1980. Hepatic cytochrome P-450 levels fall in rats exposed to cadmium (Schnell et al, 1979) and also in scorbutic guinea pigs (Omaye & Turnbull, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…fBattelle New England Laboratories, 397 Washington St., Duxbury, MA 02332, U.S.A. I83 0022-1 112/82/020183+14 $02.00/0 signs of cadmium poisoning are also found in fish. Decreased growth rates (Westernhagen et al, 1978), lowered blood iron and calcium concentrations (Larsson, 1975;Roch & Maly, 1979) and testicular injury (Sangalang & O'Halloran, 1972) in fish have been reported after cadmium exposure. However, there is little published work on the interrelationship between ascorbic acid status and cadmium toxicity in teleosts.…”
Section: Introductionmentioning
confidence: 99%
“…Of all these, mussels are known to be the most sensitive indicators to elevated concentrations of heavy metals, particularly cadmium. Within the food-chain mussels, and to a lesser extent cockles, accumulate high levels or certain heavy metals (von Westernhagen et al 1978, Buchwald et al 1985. These and other diets of waders and shorebirds are contaminated with heavy metals (Packer et al 1970, Evans & Moon 1981, Zunk 1988.…”
Section: Addressee For Reprint Requestsmentioning
confidence: 99%
“…In vertebrates and invertebrates, effects of Cd on growth (Stebbing, 1976~ Paffenh6fer, 1978yon Westernhagen et al, 1978;Stebbing & Hiby, 1979), embryo and larval development (Calabrese et al, 1973;Mirkes et al, 1978;Reish &Carr, 1978;Alderdice et al, 1979;KI6ckner, 1979;Lehnberg & Theede, 1979), and the alteration of various physiological functions (e. g. osmoregulation, excretion, respiration) (MacInnes & Thurberg, 1973;Thurberg et al, 1973;Dawson et al, 1977;Thurberg et al, 1977) and behaviour (Martin et al, 1975;Eldon & Kristoffersson, 1978) have been observed.…”
Section: General Aspects Of Toxicitymentioning
confidence: 99%